Medium Voltage Cable Health Index Integrating Diagnostic Data and Feeder Load for Reliability Assessment - Negara, Pande Putu Priyanithi Dharsania; Sudiarto, Budi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2026)
Reliable operation of medium-voltage (MV) distribution networks depends strongly on the condition of XLPE-insulated cable systems. However, existing diagnostic methods, including Partial Discharge (PD), Tan Delta (TD), and Very Low Frequency (VLF) testing, are typically interpreted in isolation, limiting their relevance to operational decision-making. This study develops a unified Health Index (HI) framework that integrates these three diagnostic parameters with feeder loading data under real field conditions. Using Min–Max normalization and dual weighting schemes, the model was applied to 33 cable segments in a tropical MV distribution network. HI values were statistically correlated with the System Average Interruption Duration Index (SAIDI) and Energy Not Supplied (ENS). Results show that the dielectric-oriented weighting scheme yields stronger correlation with SAIDI (r = 0.967, p < 0.05), while equal weighting enhances sensitivity to ENS. Although feeder loading contributes to degradation exposure, intrinsic insulation condition remains the primary determinant of health classification. High-risk segments are consistently identified under both schemes, confirming the structural robustness of the model. The proposed framework provides an empirically validated foundation for condition-based and risk-based asset management in MV distribution systems.